Profile of difficult to treat asthma patients referred for systematic assessment. (August 2016) - Radhakrishna, N.; Tay, T.R.; Hore-Lacy, F.; Hoy, R.; Dabscheck, E.; Hew, M.
Abstract: Aim: We determined the proportion of asthma patients under specialist care who remain difficult-to-treat and might benefit from systematic assessment. We additionally report the characteristics and indications for referral in 90 patients who received systematic assessment for difficult asthma. Methods: We conducted a three-month prospective audit of our hospital's general asthma clinic. We then analyzed consecutive patients over 18 months referred on for systematic assessment of difficult asthma. Results: Over 3 months, 22/166 patients (13.3%) in the general asthma clinic were considered likely to benefit from systematic assessment of difficult asthma. These patients had higher inhaled steroid requirements (890 ± 604 mg), lower lung function (FEV1: 65 ± 18%), and more often received GINA step 5 treatment (22.7%). However, 7/22 (32%) of suitable patients were not referred for assessment, mainly due to patient factors. Over 18 months, 90 patients received systematic assessment for difficult asthma, on account of poor symptom control (62%), frequent exacerbations (44%), poor lung function (42%), patient factors (29%), and diagnostic uncertainty (26%). There was a high disease burden with a mean (±SD) asthma control test score and asthma quality of life questionnaire score of 14 ± 5 and 4.26 ± 1.45 respectively. 80% fulfilled criteria for severe asthma. The majority were either atopic (66.7%) or eosinophilic (54.4%); only 15.6% were neither. Patients had a median of three extra-pulmonary comorbidities, of which most were previously unrecognised. Conclusion: One-in-eight asthma patients already under specialist care were suitable for systematic assessment of difficult asthma, but a third of these were not referred due to patient factors. Diagnostic uncertainty and patient factors were important indications for systematic assessment. Most patients who underwent systematic assessment exhibited severe asthma phenotypes potentially responsive to targeted treatment, but also had multiple comorbidities. Our results highlight the importance of management strategies to address patient factors, severe asthma biology, and concurrent contributory conditions.